Ekspresi Wajah Manusia dalam Menanggapi Kehidupan Sebagai Ide Pada Penciptaan Karya Seni Grafis - Iswandi, Heri (UNIVERSITAS INDO GLOBAL MANDIRI)
This work is titled ‘Human Face Expressions in Responding to Life as an Idea on the Creation of Graphic Art Work’. Facial expressions that arise from a person, originated from the interaction of what he sees and what is stored in his mind. In the work that is made, the visual expression of the human face drawn is more focused on Ninik Mamak. Ninik Mamak or better known as the headman is the adat leader (functional adat) in Minangkabau. Ninik Mamak's position is as a holder of sako datuk (datuak) for generations according to maternal lineage in the matrilineal system. The creator chose ninik mamak as an object on the theme raised. The work created is the result of borrowing figures from a number of ninik mamak faces in Minangkabau. Ninik mamak or better known by the name of the ruler is the traditional leader in Minangkabau. Mamin ninik's position as holder of sako datuk (datuak) is hereditary according to maternal lineage in the matrilineal system. Facial expressions born from mamak ninik will later create a response when facing a social conflict that occurs in life. Where culture and customs in Minangkabau began to erode by the development of modern times. This is aimed at introspection and awareness to the public of negative social behavior through mamak ninik's facial expressions and figures in Minangkabau. Cultivation of graphic art created using hardboard cut, hand coloring, and mixed media techniques.